Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

let x=4 -x^4 = -256 is this correct?

See more answers at
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer


To see the expert answer you'll need to create a free account at Brainly

not -x^4 = 256 because this -x^4 means -1(4)^4 not (-4)^4
Is it correct?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

it is 256
(-x)^4=256 & -(x^4)=-256
becoz instead of x u r giving 4
Does that help @moongazer ??
-4 * -4 * -4 * -4=
Becoz according to BODMAS rule first we solve brackets :)
so -x^4 = -256 is correct right?
but it is like this (-4)^4
But there is no parenthesis ?
so it is like -1(x)^4
or wat is -x*-x*-x*-x
nw give x=4
wat will the answer
just think like that
isn't that \[-4^2 \neq (-4)^2\]
why both r same
no it is not
ok.....@moongazer nw tell is this correct or not -x^4=-x*-x*-x*-x
That is wrong I think.
-x^4 = -256 for the record...
that's the question I am asking :)
so i guess it's down to a 2-on-2
why //
@lgbasallote -x^4=-x*-x*-x*-x
@Yahoo! this is -(x^4) not (-x)^4
because the exponent just affects the nearest base
look his question it is just -x^4
the ^4 is just on x...not on - too
because -x^4 is like -1(x)^4 not (-x)^4 I think this is the explanation?
i would say if (-x)^4=256 & -(x^4)=-256
-x^4 = -(x^4)
so wat is -2^2
@Yahoo! (-1)(4) so -4
-2^2 = -1 (2^2) = -1 * 4 = -4
let this be an end to these skepticisms
when there is a minus, do all the stuff before minusing
hey ..... it is like this (-x)^4=256 & -(x^4)=-256
nop visit^4^2
(-x)^4=256 -x^4 = -256 ................ agreed

Not the answer you are looking for?

Search for more explanations.

Ask your own question